Beyond the limits of solidarity in the post-pandemic university - Richard Hall (Work Organisation, Labour and Globalisation, 2024)
This article challenges a liberal analysis of higher education (HE) inside an integrated system of economic production, and instead critiques: first, how UK policymakers sought to re-engineer English HE during and after the pandemic, through governance, regulation and funding changes predicated upon accelerating a discourse of value-for-money; second, the institutional labour reorganisation that followed, and which placed complete class fractions of academic labour in a permanent state of being at risk; and third, how in continually demonstrating that it cannot fulfil the desires of those who labour within it for a meaningful work-life, the university must be transcended. In addressing the entanglement of precarity and privilege, it argues that, if the university is unable to contribute to ways of knowing, being and doing that address socio-economic, socio-environmental or intersectional ruptures, then it must go.